Антиоксидантное действие оральных аппликаций кверцетинсодержащих гелей у крыс, получавших антихеликобактерную терапию = Antioxidant effect of gels containing quercetin which were applied orally to rats treated with antihelicobacter pyloli therapy - Tomilina, T. V. (Journal of Education, Health and Sport, 2015)
Tomilina T.V. Антиоксидантное действие оральных аппликаций кверцетинсодержащих гелей у крыс, получавших антихеликобактерную терапию = Antioxidant effect of gels containing quercetin which were applied orally to rats treated with antihelicobacter pyloli therapy. Journal of Education, Health and Sport. 2015;5(2):179-186. ISSN 2391-8306. DOI: 10.5281/zenodo.15993 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A179-186 https://pbn.nauka.gov.pl/works/545172 http://dx.doi.org/10.5281/zenodo.15993 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.02.2015. УДК 616.33+342.092 Антиоксидантное действие оральных аппликаций кверцетинсодержащих гелей у крыс, получавших антихеликобактерную терапию Antioxidant effect of gels containing quercetin which were applied orally to rats treated with antihelicobacter pyloli therapy Т.В. Томилина T.V. Tomilina Харьковский национальный медицинский университет (Украина) e-mail: flavan@mail.ru Kharkov National Medical University (Ukraine) Article Aim: To determine the development of lipid peroxidation (LPO) in the tissues of rats treated with antihelicobacter pyloli therapy (AHBT) and after oral applications of gels containing quercetin. Materials and Methods: Rats received the following doses of AHBT daily during 8 days: omeprazole - 1.3 mg / kg, amoxil - 50 mg / kg of clarithromycin and - 7.5 mg / kg. Gels containing quercetin (quertulin = quercetin + inulin + calcium citrate and quertulidon = quercetin + imudon) were applied to the oral mucosa (OM) at the daily dose 0.5 ml for 11 days. Euthanasia of rats was performed on the 12th day. Malondialdehyde (MDA) and catalase activity were analyzed in the tissues of cheeks, gums, stomach, liver and blood serum; and antioxidant-prooxidant index ProAntidex was calculated as ratio of catalase acivity to MDA content. Results: It was found that in affected tissues there were high levels of MDA and low ProAntidex. Gels containing quertecin reduce the level of MDA and increase ProAntidex in the tissues, and gums were most sensitive to the gels’ action. Conclusion: Increased LPO is an important pathogenetic link in the development of complications in AHBT. Key words: antihelicobacter pyloli therapy, lipid peroxidation, quercetin. Резюме Антихеликобактерная терапия (омепразол + амоксил + кларитромицин) вызывает в тканях крыс повышение уровня МДА и снижение антиоксидантно-прооксидантного индекса АПИ. Оральные аппликации кверцетинсодержащих гелей (квертулин и квертулидон) снижают содержание МДА и повышают АПИ. Ключевые слова: антихеликобактерная терапия, перекисное окисление липидов, кверцетин.